Respuesta :

Answer:

y = 3x + 3

Step-by-step explanation:

Using slope intercept form: y = mx + b

where m is the slope(rise over run/change in y over change in x), and b is the y intercept(point where x is 0). We can derive the equation by simply using our mathmatical principles of slope and y intercept. Because our y intercept is where x is 0. Our y intercept is 3 since x is 0 when y is 3 because it touches the axis. Since y is 6 when x is one.

y = mx + b

6 = m(1) + 3

-3 -3

_________

3 = m

_________

m = 3

_________

An m of 3 means that you rise 3 every 1 run or 3y every 1x.

Therefore, our equation in slope intercept is:

y = 3x + 3